The Service Capacity of Posyandu Cadres in Stunting Mitigation Programs: A Qualitative Literature Review - Nurul Fauziah (SIGn Journal of Public Health, 2025)
The prevention of stunting in Indonesia relies heavily on the service capacity readiness of Community Health Workers (CHWs) as the primary unit of primary health care; however, in practice, they continue to face multidimensional barriers that degrade the quality of basic services. This qualitative literature review aims to analyze and formulate a typology of service capacity barriers for CHWs within cognitive-procedural, interactional-behavioral, and structural-administrative dimensions in stunting mitigation programs. The method employed is a descriptive, qualitative literature review, examining secondary data comprising three textbooks and 17 reputable journal articles with active DOIs on Crossref, which were analyzed using thematic synthesis. The synthesis results indicate that weaknesses in CHWs’ anthropometric procedural capacity stem from disparities in basic education, sociopsychological tensions in the form of parental rejection due to stigma, and the administrative workload of digital reporting unmatched by infrastructure and clear boundaries of clinical authority. In conclusion, strengthening CHW capacity requires a transition from incidental training to a continuous, multidisciplinary team mentoring model, supported by the Ministry of Health’s simplification of clinical modules and the assurance of consistent village fund budget allocations from relevant ministries to guarantee the sustainability of primary health care services at the village level.